PENERAPAN METODE QUR-ANY DALAM PENINGKATAN BTA DI SD NEGERI PETERONGAN 1 - Rozaq, Abd.; Alam, Dedi (ILJ: Islamic Learning Journal, 2023)
The Qur'anic method is an alternative method for learning the Qur'an quickly, easily and pleasantly in terms of reading, writing and translating the Qur'an and practicing it in everyday life. This method emphasizes learning to read and write the Qur'an quickly, easily and pleasantly. This research is a field research, which is qualitative in nature, the form of research is descriptive qualitative using data collection techniques namely observation, interviews, and documentation. Furthermore, data analysis is carried out using qualitative analysis. The results showed that: Application of the Qur'an Method in Improving BTA Class 2 at SD Negeri Peterongan1 includes 1. Planning for reading and writing the Qur'an, Implementation of reading and writing the Qur'an and Evaluation of reading and writing the Qur'an using the Qur'an method and factors Supporters and Obstacles in the application of the Qur-any method at Peterongan 1 Public Elementary School.